Action Research on Integrating a Blended Learning Reading Course in Higher Education - Radia Bouguebs (The Journal of Studies in Language, Culture and Society, 2024)
Adopting a Blended learning approach in higher education is often a daunting task mainly if the e-learning based instruction model is not approached for fear of obstacles that may hinder rather than advance the teaching/learning process. Developing reading skills with learners necessitates the continuous integration of multiple teaching methods and strategies. Students’ tendency for information and computer technologies encouraged the teacher-researcher to think about blending face-to-face with online instruction in the design of a reading course. This action research project was used to answer the question – how does blended learning environment impact students’ academic performance and learning engagement within the class? Accordingly, this study describes a research utilizing blended learning approach to teach reading to second year students at the Ecole Normal Supérieure “Assia Djebar”   of Constantine (ENS). The intervention was designed to fit into individual lessons needed to improve students’ reading skills mainly summarizing and responding to narrative texts and to get through their personal blended learning experience. Results of this action research may help to prove whether or not the blended learning approach has a positive impact on students’ academic achievements and learning attitudes. This is to provide solutions to the teaching/learning impediments when this approach is adopted at a tertiary level education.